Vertical vegetable garden with pet bottles for students environmental awareness construction (Research, Society and Development, 2021)
This study aims to report a research and environmental practice carried out through the construction of a vertical vegetable garden with PET bottles with students of the first year of high school, in the municipality of Urutaí-GO, southeast of the state of Goiás. A pre-test was applied to the students to assess the level of interest and concern regarding healthy eating, organic products, sustainability and organic vegetable gardens. After completing the pre-test, a class on environmental and nutritional issues was given and a vertical vegetable garden with PET bottles was made, with the participation of the students. Seedlings of lettuce, chives and mint were planted. After the activities, a post-test was applied. The results indicate that the students were more concerned with healthy eating and environmental issues after the explanatory class and the practice of building the vertical vegetable garden. It is concluded that the vertical vegetable garden contributes to the increase of interest of students for environmental and nutritional issues, which makes it a good instrument for building environmental awareness of young people.